The Impact of Digital Transformation on MSMEs Agility and Business Performance in The Modern Era - Nining, Andria; Asyrafil Mustaqmah, Sri; Ali, Helmi (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
Digital transformation has become a key driver of business development in the modern era, especially for Micro, Small, and Medium Enterprises (MSMEs). In West Sumatra, despite numerous challenges in adopting technology, digitalization offers significant opportunities to enhance organizational agility and business performance. This study aims to examine the impact of digital transformation on business agility and business performance in the modern era. Digital transformation is a crucial factor driving organizational change, improving operational efficiency, and increasing competitiveness. The study uses a sample of 120 MSMEs from various sectors in West Sumatra. A Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS) analysis was used to assess the relationships between digital transformation, business agility, and performance outcomes. The research results show that changes in information technology have a positive and significant influence on organizational performance. There is a significant positive relationship between changes in information technology and MSME business performance. Organizational performance has a positive and significant influence on MSME business performance. Business performance plays an important role as an intermediary between changes in information technology and MSME business performance in West Sumatra.